Study on the contactless data transmission for ocean underwater vertical sensor structure. Issue 3 (1st September 2016) - Wu, S.; Zhang, W.X.; Li, Z.H.; Deng, Y.; Liang, J.J.; Li, F.C.; Lan, H.
ABSTRACT: Ocean underwater vertical sensor structure is a kind of modern marine observation platform. But most of the current ocean sensors work independently, and it lacks a suitable method to assemble them in a control system. Having good expansibility and convenient structure, the ocean buoy platform with contactless data transmission technology is possible to organise a long-term, real-time and autonomous working observation network. The contactless data transmission model with a two-stage electromagnetic coupler is investigated. A prototype of communication system using the differential phase shift keying method is constructed. Due to attenuation in seawater, it is difficult to realise the long distance and low bit error rate transmission. To solve this problem, an equivalent two-terminal network model with compensation capacitor is proposed to make this contactless transmission system work at the resonance frequency. In 1000 m deep sea experiment, the sensors equipped with this vertical structure based on buoy platform show a perfect similarity of conductivity points like a commercial conductivity, temperature and depth device. It can be predicted that this underwater contactless data transmission method will be widely used to construct a multipoint distributed marine data network, and it can bring large scientific and economic values in deep sea exploration.